Traces de malemorts ou lieu de nostalgie ? Sanctification et/ou patrimonialisation d’un village noir détruit (Choco, Colombie) - Anne-Marie Losonczy (Nuevo mundo - Mundos Nuevos, 2017)
In 2002, during a violent skirmish between the FARC guerrilla and the paramilitary forces, 170 inhabitants of the black village of Bellavista on the Bojava river took refuge in the church. They all died, charred to death through a bombing that left their village in ruins. The State policy of reparation includes re-installation of the surviving villagers in a new village, built in stone and cement on the site of the former graveyard. This new village gives rise to very ambivalent perceptions, whereas many inhabitants asked from the archbishop that the ruined church, sheltering a « Mutilated Christ », should be declared a pilgrimage site. Others wish to perennize the place as it is to remain a narrative site of violent death, and yet others want to preserve the ruins of the village as a memento of the vida sabrosa, considered as bygone for ever and an object of attachment. This case sheds light on a paradoxical and little analysed aspect of local attempts of patrimonialization, that of traces of the inflicted violence. Preserving such ruins as a narrative-site, appealing to both religious ansd memorial registers, allows a fluid polyphony of interpretations and avoids cristallizing an open memory conflict around armed violence.